Globalization and Culture, Impact of Globalization on Iranian Culture - Ghadir Golkarian (Universal Journal of History and Culture, 2019)
Globalization is the word that is spoken throughout the world today. This word does not target specific dimensions. Because it has influenced not only politics but also it issues literature, economics, business, culture and social. Several decades ago, Marxist ideology was one of the hottest debates between scholars and scholars. But today, the issue of globalization that has come about since the late 20th century has led to many cultural-political, economic-political and religious-political tensions and challenges. There are, of course, different perspectives on the subject of globalization. Some of these views advocate the phenomenon of globalization, while others oppose it and consider globalization as the destruction of the cultural, political and religious diversity of the people of the world. However, the phenomenon of globalization in the 21st century is being pursued vigorously and the world of the West, and in particular the United States, is seeking to achieve it. The phenomenon of globalization affects many countries in the world. Also Iran is a country of the world affected of globalization. We see the globalization process very long ago in many political, economic and cultural terms. This effect is now also influential in Iran. Therefore, it is not possible to avoid globalization. The historical, economic, political, social and cultural aspects of globalization are of great importance. One of the important dimensions of the impact of the phenomenon of globalization is the cultural dimension. Given the fact that Iran has a very old culture, as well as the existence of religious beliefs in Iran, it has been able to create a unified national-cultural culture. In this paper, we will try to study the type of effect of the phenomenon of globalization, the extent of its impact, the impact of Iranian culture on the phenomenon of globalization and the reasons for its impact. The point that we will focus more on is the issue of cultural traditionalism in Iranian society. Because Iran is a developing country and is trying to keep pace with global positive developments in many respects. Because in other ways it can not take developmental paths. But Iranian culture resists the phenomenon of globalization, and as a result, the speed of change on the path to globalization in Iran is very little.